Synthesis of Some New 1(2H)-Phthalazinone Derivatives and Evaluation of Their Acetylcholinesterase and Butyrylcholinesterase Inhibitory Activities - Kilic, Burcu; Gulcan, Hayrettin Ozan; Yalcin, Mertcan; Aksakal, Fatma; Dimoglo, Anatoli; Sahin, Mustafa Fethi; Dogruer, Deniz Songul (Bentham Science Publ Ltd, 2017)
Some 1(2H)-phthalazinone derivatives were synthesized and their chemical structures were confirmed by H-1-NMR, C-13-NMR, mass and elemental analysis. Subsequently, modified Ellman's method was used to determine both acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) inhibitory activities of the synthesized compounds. The activity results showed that compound 8c was the most active AChE inhibitor with inhibition value of 63% at 100 mu M among the tested compounds. In addition, docking of the synthesized compounds into the active sites of AChE and BuChE was carried out in order to predict the binding energies and non-covalent interactions stabilizing the enzyme-ligand complexes.
Keywords: Alzheimer's disease; 1(2H)-phthalazinone; acetylcholinesterase inhibitory activity; butyrylcholinesterase inhibitory activity; Ellman's method; molecular docking